Effects of dietary α-tocopherol acetate and pomegranate peel extract on growth performance and antioxidative potential and lipid oxidation of meat of broiler - Sarica, Ş; Erinc, H; Aydin, H (Journal of the Hellenic Veterinary Medical Society, 2023)
The study compared the effects of dietary supplementation of pomegranate peel extract (PPE) alone or in combination with α-tocopherol acetate (TA) on the performance, carcass traits, serum and meat parameters of broilers. The diets included: CONT: a control diet containing 50 mg/kg TA and 4 % flaxseed oil; TA200: the diet supplemented with 200 mg/kg TA to the control diet; PPE100, PPE200 and TA100+PPE100: the diets supplemented with 100 and 200 mg/kg PPE and 100 mg/kg TA+100 mg/kg PPE to the CONT diet. The dietary treatments had no significant effect on growth performance, internal organ weights and carcass yields. The TA200, PPE100, PPE200 and TA100+PPE100 diets significantly reduced the levels of lipid hydroperoxide and total oxidant and significantly increased the antioxidant level of the serum of broilers. The TA200, PPE100, PPE200 and TA100+PPE100 diets significantly increased the contents of total polyunsaturated fatty acids, omega-6 FAs and omega-3 FAs, total phenolic contents, DPPH radical scavenging activity and ferric reducing power, and significantly decreased the concentrations of total saturated fatty acids, total monounsaturated fatty acids, the omega-6:omega-3 ratio and the MDA value of the thigh meat and breast meat compared to the CONT diet. In conclusion, the antioxidant potential and lipid oxidation stability of broiler meat may be improved by supplementing the diet with TA or PPE alone or in combination. Moreover, the antioxidant potential of TA and PPE in combination in the diet was more strong in refrigerated broiler meat enriched with omega-3 PUFAs than that of TA alone.